New trends in biological aids to recovery after exercise: Immunomodulators - Córdova Martinez, A.; Fernández-Lázaro, D. (Journal of Human Sport & Exercise, 2018)
The professional sport increases the physical and biochemical demands of muscle that is accompanied by important metabolic changes, such as the accumulation of toxic compounds, increased consumption of nutrients, and alterations in the physical, thermal and mechanical conditions of the cells. Neuroendocrine adaptations to the demands of elite athletic activity also modify local and systemic immune function, which contributes to the development and continuation of the inflammatory response. During intensive training and competition days, the recovery needs are also impressive. In such circumstances, athletes need to ingest often supplements as protein, micronutrients, minerals or substances to improve the muscular recovery In our experience, many specific products as the immunomodulators are directly linked to benefits, such as improved performance and concentration, reduced fatigue, better recovery and improved health or resistance against minor infections, which seem to occur more often when athletes are undergoing very intensive training. The purpose of this review is to provide an update on published research focusing primarily on the efficacy of immunomodulation substances in the recovery of athletes with respect to physical performance.